Generic framing procedure (GFP) the catalyst for efficient data over transport. - Bonenfant, P. (IEEE Communications magazine)
We discuss the generic framing procedure (GFP) in the context of emerging nontraditional data over transport applications. Coupled with complementary efforts to define virtual concatenation, automatic link capacity adjustment schemes, and distributed control planes for transport networks, we contend that GFP serves as the catalyst for efficient and standard data over transport service offerings.